Analisis Strategi Pemasaran Dalam Upaya Meningkatkan Penjualan Pada Brand Casual Culture.Co - Muhammad Fernanda Raditya Pradipa; H. Abdul Manan; Komarun Zaman (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The purpose of this study is to find out how the marketing strategies carried out by Casual Culture.co brands to increase sales. This type of research uses qualitative research. This study used primary data. The data collection techniques used in this study were observation, interviews and documentation. The results of this study show that the marketing strategy carried out is to use attributes on products that include quality, design, service, price and brand. From the research on marketing strategies carried out by Casual Culture.co less optimal and less efficient, therefore the author provides advice or input to implement aggressive marketing strategies to increase sales volume so as to get maximum profits.